I’JAZ NUBUATAN DALAM AL-QUR’AN: KAJIAN PUSTAKA PERSPEKTIF KLASIK DAN KONTEMPORER - Nur Muhammad Habibbullah Azzuhri; Muhammad Ali Musthofa Kamal (Al-Iqro', 2026)
This study examines the concept of prophetic i‘jaz in the Qur’an as one of the dimensions of its miraculous nature that affirms the truth of divine revelation and the prophethood of Muhammad (peace be upon him). Prophetic i‘jaz refers to Qur’anic statements concerning future events that were later historically verified, such as the prophecy of the Roman victory over the Persians mentioned in Surah ar-Rum (30:2-4). This research employs a library-based qualitative approach by analyzing classical and contemporary scholarly works addressing Qur’anic i‘jaz from linguistic, historical, and scientific perspectives. The findings indicate that prophetic i‘jaz plays a crucial role in strengthening Islamic creed, legitimizing the prophethood of Muhammad, and affirming the Qur’an as a divine scripture beyond human authorship. Furthermore, prophetic i‘jaz demonstrates the timeless relevance of the Qur’an and serves as a rational approach to Islamic preaching by integrating faith with reason and historical evidence. Therefore, prophetic i‘jaz holds not only theological significance but also epistemological and methodological implications for contemporary Qur’anic studies.